Innovation and strategy of online games - Jong, H. Wi (Series on technology management, 2009)
This book is the first study to survey, over a ten-year period, innovations and the industrial formation process of online game business, and global strategies of major Korean online game companies. It focuses on the innovative factors which made the Korean online game industry grow tremendously and successfully to gain competitiveness in the global game industry. These include: the main factors stimulating online game business; virtual business created by online games as well as an examination of the role of the Korean government at the beginning and developmental period of the online gaming business. This book also contains authentic and accumulated research conducted over five years in the international domain of the online game industry. This research unveils diverse strategies of game companies and presents cognitive differences toward the online game business where various convergences will occur between the online game and other Internet businesses.